2022
DOI: 10.51329/mehdiophthal1449
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Postnatal Growth and Retinopathy of Prematurity (G-ROP) screening criteria

Abstract: Background: Retinopathy of prematurity (ROP) is a leading cause of irreversible blindness in infants. The Postnatal Growth and ROP (G-ROP) study proposed new screening criteria for ROP. This study aimed to validate the G-ROP screening criteria in a group of Iranian premature infants who were treated in the neonatal intensive care unit (NICU) for at least 40 days. Methods: In this retrospective study, we extracted the data pertaining to infants admitted to the NICU from January 2020 to December 2021. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…On the other hand, studies from socio-economically developing countries, such as Egypt, Iran, Thai, and another study from Turkey, reported the sensitivity for treated and Type 1 ROP was 100%, similar to ours (Ahmed et al, 2022;Fadakar et al, 2022;Okbay Gunes et al, 2022;Trinavarat et al, 2023) (Table 2). Furthermore, in a study from China, three severe ROP cases missed by GA and BW criteria were detected by the WG criterion (Lu et al, 2023).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, studies from socio-economically developing countries, such as Egypt, Iran, Thai, and another study from Turkey, reported the sensitivity for treated and Type 1 ROP was 100%, similar to ours (Ahmed et al, 2022;Fadakar et al, 2022;Okbay Gunes et al, 2022;Trinavarat et al, 2023) (Table 2). Furthermore, in a study from China, three severe ROP cases missed by GA and BW criteria were detected by the WG criterion (Lu et al, 2023).…”
Section: Discussionsupporting
confidence: 87%
“…(2018). A sensitivity rate of 100% for Type 1 ROP or for treated ROP was also achieved in different populations such as the UK, Egypt, Switzerland, Japan, the USA, Iran, Thai, Turkey, and Italy (Ahmed et al., 2022; Caruggi et al., 2021; Fadakar et al., 2022; Okbay Gunes et al., 2022; Shiraki et al., 2019; Trinavarat et al., 2023; Vinayahalingam et al., 2022; Wadley et al., 2020) (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…In a similar study by Fadakar et al from Iran, it was shown that G-ROP screening criteria can achieve a sensitivity of 97.6%, and of 36 infants without ROP, whereas 3 infants were correctly excluded (specificity = 8.3%). The G-ROP criteria did not fail to identify infants who required treatment for ROP (sensitivity, 100%) and had a specificity of 8.69% [ 1 ]. A similar study from Egypt applied the G-ROP model to 605 premature infants and reported 100% sensitivity with a median GA of 31.5 wk and median BW of 1200 gm.…”
Section: Discussionmentioning
confidence: 99%
“…Retinopathy of prematurity (ROP) is one of the leading causes of preventable loss of vision in premature babies worldwide and disproportionately affects premature babies in low- and middle-income countries (LMICs) like Pakistan [ 1 ]. Improved neonatal care in LMICs has undeniably led to a rise in the survival rates of preterm and low birth weight infants [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although BW and GA are quite important in terms of ROP risk, we observed an absence of association with blood flow. This may be explained by the previous literature that indicates some contribution to ROP risk is also related to post-natal growth 35 . In terms of GA, we found that the chronological age has a stronger association with blood flow.…”
Section: Discussionmentioning
confidence: 84%